2013
DOI: 10.5370/jeet.2013.8.6.1512
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Electrical Aging on Space Charge Dynamics of Oil-Impregnated Paper Insulation under AC-DC Combined Voltages

Abstract: -Oil-impregnated paper is a major type of insulation used in oil-filled converter transformers for both traditional and new energy systems. This paper presents and analyzes the results of the experiment conducted on the electrical aging of oil-impregnated paper under AC-DC combined voltages using the pulsed electro-acoustic (PEA) technique. The formation and dynamics of space charge affected the performance of insulation material. The electrical aged oil-paper insulation was obtained through electrical aged ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Under the higher applied electric fields at the higher temperature, a large amount of hetero space charges was detected earlier after the voltage application [8]. In addition, more charges are found trapped in the bulk of an aging sample after a long time of electrical aging time [9].…”
Section: Introductionmentioning
confidence: 99%
“…Under the higher applied electric fields at the higher temperature, a large amount of hetero space charges was detected earlier after the voltage application [8]. In addition, more charges are found trapped in the bulk of an aging sample after a long time of electrical aging time [9].…”
Section: Introductionmentioning
confidence: 99%
“…Reference [5] estimated the degree of polymerization (DP) and percentage of moisture content (PMCs) in oil-impregnated paper insulation using dielectric response sensing obtained from frequency-domain spectral tests. The insulating paper aging platform constructed in reference [6] studied the microstructure and electrical characteristic changes in insulating paper under different AC/DC composite voltages and found consistency in the degradation mechanism and microstructure of insulating paper under different composite voltages. In reference [7], accelerated thermal aging experiments were carried out on insulating paper at 120 • C and 130 • C, respectively, and the results showed that the crystallinity index and refractive index of cellulose fiber in insulating oil could be used as feasible indexes for the diagnosis of paper degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Oil-paper insulation is one of the major types of insulation in converter transformers. Valve-side windings of HVDC converter transformers were subjected to pulsating DC voltage stresses consisting of AC, DC and strong harmonic components [3][4][5]. With the increase of the transmission voltage rating, partial discharges (PDs) will happen in the weak insulation of converter transformer.…”
Section: Introductionmentioning
confidence: 99%